Analisis Dakwah : Komunikasi Dakwah Ismail Al-Kholili Melalui Media Sosial Instagram - Fina Mahzuni Azki Sururi (STIKes Ibnu Sina Ajibarang, 2025)
In da'wah activities, language plays a crucial role as a means of communication that can be understood by every person or target of da'wah. Clear, simple, and communicative language will facilitate da'wah practitioners in conveying religious messages to the community. Da'wah communication is not limited to the use of verbal symbols such as words, but also includes nonverbal symbols that can strengthen the meaning of the da'wah message itself. Along with the development of information technology, da'wah media has also undergone significant changes. While da'wah was previously carried out through religious study groups, mosques, and face-to-face forums, social media has now emerged as a new, effective platform for conveying da'wah messages. One widely used social media platform is Instagram. This medium has a strong visual character, prioritizing images, videos, and short texts that are easily accessible to users. This is a unique attraction for da'wah practitioners in conveying religious messages to a wider audience, especially the younger generation who actively use Instagram. Through features such as feed uploads, Instagram Stories, and live broadcasts, da'wah can be packaged in a more creative, engaging, and relevant way to meet the needs of today's mad'u. One figure who utilizes Instagram as a means of da'wah is Ismail Amin Al-Kholili. Ismail's approach emphasizes the importance of da'wah communication that is appropriate to the context of the mad'u. In terms of message interaction, his da'wah can be studied through several forms of communication, namely da'wah bil-hal, da'wah bil-lisan, and da'wah bil-khitbah. Da'wah bil-hal is seen in the actual practice of behavior and exemplary behavior displayed, da'wah bil-lisan through lectures or advice delivered in audio-visual form, while da'wah bil-khitbah is seen in the delivery of short sermons that are packaged concisely and easily understood.